The Analysis of the Causal Factors of Consumers’ Intension to Choose Online Retail Channel - Sombultawee, Kedwadee; Weeraphattarawanich , Phattarapron (Human Resource and Organization Development Journal, 2021)
This study aims to examine the consumers’ intention to choose online retail channel, focuses on the quality of the online store consisting of system quality, information quality and service quality which will result in consumers' perceived behavioral control and perceived risk. Also, this study examines the influence of online channel price advantage affecting online channel selection intention. The empirical analysis through the survey of Thai consumers between the ages of 18 - 36 who have experienced buying products online. Data were collected by using online questionnaires and data analyzed using Structural Equation Model (SEM). The result shows that online stores with quality system and information positively effect on consumers' perceived behavioral control. Furthermore, customers' perceived behavioral control positively impacts on the intention of choosing the online stores. We hope that the results of this study will guide entrepreneurs or online channel managers to implement in planning the structure for online channel development leading to increase the competitiveness.